2021
DOI: 10.1002/solr.202100869
|View full text |Cite
|
Sign up to set email alerts
|

Nanoepitaxy Growth of Sb2Se3 Nanorod Arrays on Mixed‐Oriented Transparent Conducting Oxide‐Coated Glass for Efficient and Quasiomnidirectional Solar Cells

Abstract: Low‐symmetric and structurally anisotropic materials are of widespread research interest. Antimony selenide and analogues from group V2−VI3 metal chalcogenides, have emerged recently due to their distinctive crystalline symmetries, highly anisotropic electronic and physical properties, Earth abundance, and environmentally friendly characteristics. Its intrinsic quasi‐1D crystal structure leads to much easier and efficient carrier transport along the [hk1] orientation than in other directions. Effective manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For CSS, the contribution of source radiative heating to the surface thermal energy is significant, as the substrate reaches a temperature as high as 250 °C without any substrate heating. [26] The actual temperature of the substrate could reach as high as 370-380 °C during the deposition of high-quality Sb 2 Se 3 absorber layers. In this case, Sb 2 Se 3 nanorods along the c-axis could be obtained in tens of seconds due to its strong anisotropy in bonding property.…”
Section: Resultsmentioning
confidence: 99%
“…For CSS, the contribution of source radiative heating to the surface thermal energy is significant, as the substrate reaches a temperature as high as 250 °C without any substrate heating. [26] The actual temperature of the substrate could reach as high as 370-380 °C during the deposition of high-quality Sb 2 Se 3 absorber layers. In this case, Sb 2 Se 3 nanorods along the c-axis could be obtained in tens of seconds due to its strong anisotropy in bonding property.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between these results demonstrates that the pulse length and radiant energy were crucial in orientation preference. Due to the quasi-one-dimensional crystal structure of Sb 2 Se 3 , films with the ( hkl , l ≠ 0) orientations (i.e., oriented in the (211) and (221) directions) are preferred for PV applications due to better carrier transport and collection through the absorber layer. Therefore, tuning PC parameters for a 10 ms pulse length can form films with these preferred orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Antimony selenide (Sb 2 Se 3 ) has emerged as a strong candidate for thin film solar cell applications and water splitting devices with a current power conversion efficiency (PCE) of 10.57% for photovoltaics. Currently, almost all Sb 2 Se 3 solar cells with high PCE are fabricated by physical vapor deposition at high temperatures (>300 °C) to obtain crystalline Sb 2 Se 3 with (211)- and (221)-oriented thin films (space group Pnma (62)), which are favorable for carrier transport. Postdeposition annealing techniques are often used to improve the absorber quality (i.e., to increase crystallinity, tune nanoribbon orientation, decrease nonradiative recombination loss, and reduce the bulk trap density), which takes 30 to 120 min. Because of this, optimization of production throughput by eliminating rate-limiting equilibrium thermal annealing steps is essential to lower the manufacturing cost of device fabrication. In addition, high-temperature annealing causes mechanical failure in flexible substrates due to the mismatch in thermal expansion coefficient between different layers. , Therefore, thermal treatment is undesirable in terms of stability, cost, high volume commercial production, and roll-to-roll manufacturing of such devices.…”
Section: Introductionmentioning
confidence: 99%
“…In [39], another CSS growth was adopted to obtain Sb2Se3, and the authors found that the formation of the Sb2Se3 crystal was not strongly dependent on the substrate temperature. However, (hk0) planes, parallel to the substrate, decreased for growth C. Guo et al [45] studied the incorporation of a Ag element into Sb 2 Se 3 obtaining quasi-vertical 1D ribbons at 280 • C, which vanished at 420 • C, where the (120) preferential orientation prevailed.…”
Section: One-dimensional-ribbon Alignmentmentioning
confidence: 99%
“…In [39], another CSS growth was adopted to obtain Sb 2 Se 3 , and the authors found that the formation of the Sb 2 Se 3 crystal was not strongly dependent on the substrate temperature. However, (hk0) planes, parallel to the substrate, decreased for growth temperature >240 • C (up to 410 • C), while most of the TCs for the (hk1) planes, oblique or perpendicular to the substrate, increased with the growth temperature between 240 • C and 410 • C. Σ TC(hk ) = 0 was 92.2% in this case and AZO/i-ZnO/CdS/Sb 2 Se 3 /FTO/glass solar cells with a 1350 nm (Figure 4b,c) thick Sb 2 Se 3 layer demonstrated a J sc of 29.5 mA/cm 2 and a conversion efficiency of 9.0%.…”
Section: One-dimensional-ribbon Alignmentmentioning
confidence: 99%